The Incidence and Natural History of Forefoot Scar Pain Following Open Hallux Valgus Surgery. Issue 4 (August 2013) - Ieong, Edmund; Afolayan, John; Little, Nicholas; Solan, Matthew; Pearce, Christopher
Background . Scar symptoms are a recognized complication of forefoot surgery. The aim of our study was to quantify and qualify these symptoms following open Scarf osteotomy for hallux valgus.Methods . A total of 125 consecutive patients with a minimum of 1 year's follow-up were questioned, with a response rate of 82%. Four patients were excluded because of superficial wound infections, leaving 98 patients in the study.Results . In all, 30 patients (31%) reported scar symptoms. In this symptomatic group, 8 patients (21%) undertook noninvasive intervention for their symptoms, and the remaining 22 symptomatic patients (79%) did not use any form of intervention for their symptoms. Patients who undertook some sort of intervention had a significantly shorter duration of symptoms (mean = 19 vs 44 weeks; P = .01). The mean duration of symptoms was 27.9 weeks, and mean symptom score was 3 out of 10. At the 1-year follow-up, 95% of patients had no scar symptoms. There was no significant difference in either the preoperative severity of the deformity or the degree of correction achieved between the symptomatic and asymptomatic patients.Conclusion . These results can be used to obtain consent, educate, and reassure patients. We recommend simple noninvasive interventions should patients experience postoperative scar symptoms. Levels of Evidence : Therapeutic, Level IV